Type III secretion system genes hrcJ and hrpE affect virulence, hypersensitive response and biofilm formation of group II strains of Acidovorax citrulli - Wang, Tielin; Huang, Qi; An, Xin; Yang, Yuwen; Guan, Wei; Zhao, Tingchang (Frontiers in Sustainable Food Systems, 2022)
Bacterial fruit blotch (BFB) caused by Acidovorax citrulli is a worldwide threat to watermelon and melon production. The type III secretion system (T3SS) plays an important role in the virulence of A. citrulli in its host plants and to induce hypersensitive response (HR) in its non-host plants. Little is known, however, about the contribution of the T3SS to biofilm formation in A. citrulli. We mutated two T3SS-related genes hrcJ and hrpE, respectively, and compared the mutants with their wild-type strain Aac-5 of A. citrulli, and their complementation strains on virulence, HR, and biofilm formation. Both mutants significantly reduced virulence in watermelon and melon seedlings and their ability to induce HR in tobacco leaves. Such reduction phenotypes were significantly recovered to the wild-type level, when the mutant strains were complemented with the wild-type hrcJ and hrpE genes. Interestingly, the two T3SS-related gene mutants also displayed enhanced ability to form biofilm, suggesting a different role of biofilm in the virulence of the group II stains of A. citrulli.